National treatment outcome and predictors of death and treatment failure in multidrug-resistant tuberculosis in Ethiopia: a 10-year retrospective cohort study - Mohammad Ali Mansournia; Mehdi Yaseri; Habteyes Tola; K Holakouie-Naieni; Dinka Fikadu Gamtesa; Ephrem Tesfaye; Zemedu Mahamed; Million Molla Sisay (BMJ Open)
Objectives Treatment success rate in patients treated for multidrug-resistant tuberculosis (MDR-TB) is low, but predictors of treatment failure and death have been under-reported. Thus, we aimed to determine the national proportion of treatment success rate in the past 10 years and factors that predict treatment failure and death in patients with MDR-TB in Ethiopia.Setting A retrospective cohort study with a 10-years follow-up period was conducted in 42 MDR-TB treatment-initiating centres in Ethiopia.Participants A total of 3395 adult patients with MDR-TB who had final treatment outcome and who were treated under national TB programme were included. Data were collected from clinical charts, registration books and laboratory reports. Competing risk survival analysis model with robust standard errors (SE) was used to determine the predictors of treatment failure and death.Primary and secondary outcomes Treatment outcome was a primary outcome whereas predictors of treatment failure and death were a secondary outcome.Results The proportion of treatment success was 75.7%, death rate was 12.8%, treatment failure was 1.7% and lost to follow-up was 9.7%. The significant predictors of death were older age (adjusted hazard ratio (AHR)=1.03; 95% CI 1.03 to 1.05; p<0.001), HIV infection (AHR=2.0; 95% CI 1.6 to 2.4; p<0.001) and presence of any grade of anaemia (AHR=1.7; 95% CI 1.4 to 2.0; p<0.001). Unlike the predictors of death, all variables included into multivariable model were not significantly associated with treatment failure.Conclusion In the past 10 years, although MDR-TB treatment success in Ethiopia has been consistently favourable, the proportion of patients who died is still considerable. Death could be attributed to advanced age, HIV infection and anaemia. Prospective cohort studies are necessary to further explore the potentially modifiable predictors of treatment failure.